On the Sequential Choice of Tradable Permit Allocations - Ian A. MacKenzie (ETH Zurich, CER-ETH - Center of Economic Research, 2008)
This paper investigates the sequential announcement of domestic emissions caps by regulators in a federal or international-based tradable pollution permit market for a transboundary pollutant. A leader-follower framework is used to analyse the consequences of regulators sequentially announcing domestic allocation caps. We find the sequential choice of domestic allocation caps is sub-optimal and depends on the follower's reaction to the leader's choice. Furthermore, the marginal damage and the degree to which allocations are substitutes or complements affects whether the leader changes from being a net permit buyer (seller) of permits to a seller (buyer).
Keywords: D78; L13; Q28; 330; Initial allocation; international tradable permit market; leader-follower; Emissionshandel; Grenzüberschreitende Umweltbelastung; Allokation; Duopol; Nash-Gleichgewicht; Theorie